Babrius and Phedrus - Babrio; Ben Edwin Perry; Fedro (Cambridge (Mass.); London Harvard; Heinemann, 1984)
Ben Edwin Perry (intr. stor.). Ed. bilingue
Edizioni San Paolo srl - Piazza Soncino, 5 - 20092 CINISELLO BALSAMO (MI) (non commercial uses only) ® Copyright 2018